Synthesis of novel Nucleoside Analogues from Imidizoline and Evaluation their Anti microbial Activity - M. Al-Mouamin , Thanaa; J. Mehdi, Dehyaa (Iraqi Journal of Science, 2023)
In this research some new nucleoside analogues were synthesized. Starting from α-D- glucose which was protected to glucose penta acetat α-D- glucose pyronside (1). Which was converted to active form 1-bromo protected sugar (2) as a sugar moiety. The base moiety 2-substituted imidazoline (3,4) was prepared from condensation of ethylene diamine with two kind of aromatic aldehydes, which were subjected to amino alkylation via Mannich reaction forming new nucleaobase derivatives (5-10). Condensation of nucleobase with bromo sugar through nucleophilic substitution of anomeric carbon with nitrogen forming new protected nucleoside analogues (11-16). De blocking of these nucleoside analogues with sodium methoxide in methanol afforded our target the free nucleoside analogues (17-22).All prepared compounds were identified by FT-IR and some of them with 1H-NMR and 13C-NMR spectroscopy. Some of synthesized nucleoside analogues were screened for their antibacterial activity against four types of bacteria, also against four types of fungi.